Atribut Islami dan Religiusitas : Implikasinya pada Loyalitas Konsumen Skincare dan Kosmetik Halal - Rusdi, Wahyudi; Putra, Farhan Soekarno; Podomi, Hestika; Nugroho, Moh Agus (IAIN Langsa, 2025)
This study aims to contribute to the understanding of how Islamic attributes and religiosity influence consumer satisfaction and loyalty in halal skincare and cosmetic products. The research employed a survey method with questionnaires distributed via social media, targeting a sample of 190 individuals selected using purposive sampling. Data were analyzed using SEM with PLS software. The study found that both general and Islamic attributes significantly enhance consumer satisfaction, which is crucial for businesses in Islamic markets. However, Islamic religiosity does not significantly affect the relationship between satisfaction and loyalty, indicating that product quality and service are more important for building consumer loyalty. Businesses should focus on other aspects to strengthen loyalty in Islamic markets.